2010
DOI: 10.1007/s10916-010-9606-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Arthritis Through Fuzzy Inference System

Abstract: Expert or knowledge-based systems are the most common type of AIM (artificial intelligence in medicine) system in routine clinical use. They contain medical knowledge, usually about a very specifically defined task, and are able to reason with data from individual patients to come up with reasoned conclusion. Although there are many variations, the knowledge within an expert system is typically represented in the form of a set of rules. Arthritis is a chronic disease and about three fourth of the patients are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…Singh et al [21] 2010 Fuzzy inference system for diagnosis of arthritis. Inflammation of joints have many root causes, and the investigations are time consumingtaking and quite costly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Singh et al [21] 2010 Fuzzy inference system for diagnosis of arthritis. Inflammation of joints have many root causes, and the investigations are time consumingtaking and quite costly.…”
Section: Methodsmentioning
confidence: 99%
“…Recent literature could not review any such study where the principle of AIM has been applied in PMS diagnosis. However, in other complex domains, such as dentistry, joint disorders, gynecology, mental health, etc., where similar clinical vagueness prevails, AIM techniques have been applied [19][20][21][22][23]. Table 1, below shows some of the techniques used, and the context of the study in a concise manner just to yield a glimpse of how various AIM techniques have been used to engineer meaningful information and knowledge from clinical ambiguities.…”
Section: Brief State Of Artmentioning
confidence: 99%
“…A study encompassing a literature review, best practice guidance and views of expert informants suggested that high quality PCP care would need to fulfil two core aspects of care and management of patients with arthritis – first early recognition of symptoms and second a prompt referral to a specialist for diagnosis, ideally within the first or second consultation 76. However, it has been reported that <50% are referred to a specialist within 3 months5 49 and that people with RA may visit their PCP an average of four times before being referred. Lack of knowledge and awareness and lack of incentives for payment and quality measures have been reported as factors contributing to the delays.…”
Section: Discussionmentioning
confidence: 99%
“…An automated system was developed using a self-organizing fuzzy rule-based system [2]. According to [12], Arthritis is a chronic disease and about three fourth of the patients are suffering from osteoarthritis and rheumatoid arthritis which are undiagnosed and the delay of detection may cause the severity of the disease at higher risk. A system for the diagnosis of Arthritis using fuzzy logic controller (FLC) was designed which was, a successful application of Zadeh's fuzzy set theory [16].…”
Section: Review Of Literaturesmentioning
confidence: 99%
“…A system for the diagnosis of Arthritis using fuzzy logic controller (FLC) was designed which was, a successful application of Zadeh's fuzzy set theory [16]. It is a potential tool for dealing with uncertainty and imprecision [12]. [10], designed a decision support system for malaria and dengue (DSSMD).…”
Section: Review Of Literaturesmentioning
confidence: 99%